2012
DOI: 10.1371/journal.pone.0035780
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Analysis and Risk Factors for Escherichia coli Producing Extended-Spectrum β-Lactamase Bloodstream Infection in Hematological Malignancies

Abstract: IntroductionPatients with hematologic malignancies have greater risk-factors for primary bloodstream infections (BSI).MethodsFrom 2004–2009, we analyzed bacteremia caused by extended-spectrum beta-lactamase Escherichia coli (ESBL-EC) (n = 100) and we compared with bacteremia caused by cephalosporin-susceptible E. coli (n = 100) in patients with hematologic malignancies.ObjectiveTo assess the clinical features, risk factors, and outcome of ESBL-EC BSI in patients with hematologic malignancies, and to study the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
45
3
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(55 citation statements)
references
References 27 publications
6
45
3
1
Order By: Relevance
“…This is consistent with a previous study that found an increased risk of bacteremia by ESBL-EC in patients colonized with ESBL-EC with a RR=4.5 (95 % CI 2.89-7.04) [1]. The higher risk to BSI by ESBL-EC of the same colonizing strain may be related with HM type; thus, therapy for primary disease: aggressive myelosuppressive chemotherapy; profound neutropenia, and the use of broad-spectrum antibiotics, consistent with previous findings [15,16,23,24]. It has been reported that acute myelogenous leukemia and prior treatment with platinum analogues or quinolones are independent risk factors for ESBL-EC BSI in colonized patients [25].…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…This is consistent with a previous study that found an increased risk of bacteremia by ESBL-EC in patients colonized with ESBL-EC with a RR=4.5 (95 % CI 2.89-7.04) [1]. The higher risk to BSI by ESBL-EC of the same colonizing strain may be related with HM type; thus, therapy for primary disease: aggressive myelosuppressive chemotherapy; profound neutropenia, and the use of broad-spectrum antibiotics, consistent with previous findings [15,16,23,24]. It has been reported that acute myelogenous leukemia and prior treatment with platinum analogues or quinolones are independent risk factors for ESBL-EC BSI in colonized patients [25].…”
Section: Discussionsupporting
confidence: 87%
“…This phenomenon has been reported to occur in between 7 and 15 % in different settings, such as older patients with intestinal obstruction, chronic liver disease, or after abdominal surgery [20][21][22], but there have been scarce reports in patients with neutropenia. In a previous report on 63 (29 %) patients colonized with ESBL-EC of 217 patients with HM and neutropenia, only one developed BSI by ESBL-EC and eight by non-ESBL-EC [23]. We found 17 patients initially classified as colonized by non-ESBL-EC who switched during follow-up (mean days, 102 days) to an ESBL-EC strain.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Aunado a lo anterior, el retraso en el inicio de antibióticos específicos puede también ser un factor relacionado con la mortalidad. 2 Las infecciones por microorganismos MDR incrementan la morbimortalidad, los días de estancia hospitalaria y los requerimientos en el uso de antibióti-cos de amplio espectro, asociados también con mayores costos de atención y otras complicaciones secundarias como colitis por Clostridum difficile.…”
Section: Salud Pública De México / Vol 60 No 2 Marzo-abril De 2018unclassified
“…Over the past few years, a remarkable increase has been reported in the number of ESBL-E. Coli-associated bloodstream infections in several parts of the world (13,14). Furthermore, in cancer patients with prolonged hospitalization and with ALL who had received antibiotics for a prolonged period, the opportunity for these bacteria to cause infections enhances (14).…”
Section: Discussionmentioning
confidence: 99%